ANALYSIS OF THE RELATIONSHIP BETWEEN ORGANIZATIONAL CULTURE AND COMPENSATION ON TEACHER PERFORMANCE IN EDUCATIONAL INSTITUTIONS: A LITERATURE REVIEW - Rizal Oktadiono, Moh.; Rindaningsih, Ida (PT. Antis International Publisher, 2025)
Objective: The study aims to understand the impact of organizational culture and compensation on teacher performance. Teacher performance is a critical factor in determining the quality of education in educational institutions. Highly performing teachers not only deliver lessons effectively but also motivate and inspire students to achieve their full potential. Method: This research employs the Systematic Literature Review (SLR) method. Data collection involved formulating research questions, collecting 15 relevant articles, filtering them to 5 articles aligned with the research objectives, conducting a comparative review focusing on the results section, presenting the data, and drawing conclusions from the findings. Results: The study concludes that both organizational culture and compensation collectively have a significant impact on enhancing teacher performance. This conclusion is based on a synthesis of findings across the reviewed literature. Novelty: The study offers a focused analysis of the combined influence of organizational culture and compensation on teacher performance through a systematic literature review approach, providing a comprehensive understanding of these interrelated factors.